Pengaruh Jangkauan Pasar, Skala Produksi Dan Panjang Saluran Pemasaran Terhadap Preferensi Petani Untuk Memiliki Sertifikasi Organik - Novita Novita; Fahrul Riza (Business Management Journal, 2018)
Indonesia is one of the Ten Countries with Largest Organic Area 2012 in Asia. Permentan No. 64 tahun 2013 on organic certification aims to make organic farmers protected in their organic activities. But the fact is, the number of uncertified organic farmers in Indonesia is still high at 48%. The purpose of this research is to know the influence of market concentration, scale of production and length of product chain to preference by using logistic regression model. Respondents in this study are 100 organic producers that have uncertified organic land.Keywords: organic certification, preference, market concentration, scale of production, length of product chain